Course offers in adult education in the context of migration and flight—results and conclusions from the example of adult education centers in North Rhine-Westphalia - Halit Öztürk (Zeitschrift für Weiterbildungsforschung - Report, 2018)
Abstract Adult education centers (“Volkshochschulen”) realize their educational mission nationwide, in a wide range of educational topics and for all citizens. In order to foster equal participation opportunities for all population groups, they face the challenge of adapting their work to social developments. Organizational approaches such as diversity management and intercultural opening provide a framework that considers different levels of continuing education work and discusses their contribution to the recognition, appreciation and inclusion of social diversity within and outside the organization. Migration and flight are topics that have experienced a new wave of attention in recent years. The article focuses on the arrangement of programs and course offers for adults with a so-called migration background at adult education centers in North Rhine-Westphalia. From an empirical review of organizational measures in the context of migration carried out in 2016, the article presents selected results, supplemented by a website content analysis. In order to view the arrangement of course offers as an integrated part of continuing education work at adult education centers, some results are also presented at the analysis levels of the staff and the organization. Finally, concrete challenges are identified at all three levels.